Psychological status and its clinical determinants among people living with HIV/AIDS (PLWHA) in Northern Peninsular Malaysia - Mohd Radzniwan A Rashid; Alyani M.; Aida J.; Khairani O.; Nik Jaafar N.R.; Tohid H. (Urban and Partner, 2024)
Aim To determine the prevalence of depression, anxiety and stress, and its associated sociodemographic and clinical factors among people living with HIV/AIDS (PLWHA). Background The number of PLWHA with a near-normal life expectancy has been increasing. This has led them to face various challenges living with the disease, exposing them to multiple psychological problems. Materials and methods This was a cross-sectional study conducted at an HIV clinic in a government hospital in Northern Peninsular Malaysia. A total of 206 PLWHA were recruited using systematic random sampling. Sociodemographic factors and presence of negative emotional states were recorded using a self-administered questionnaire comprising the Depression, Anxiety and Stress Scale 21 (DASS-21). Results The prevalence of depression, anxiety and stress were 36.9%, 45.1% and 26.7% respectively. The majority had moderate to extremely severe symptoms of depression (71.1%), anxiety (88.2%), and stress (72.27%). After controlling for cofounders using multiple logistic regression, those with a co-morbidity had 3.02 times the odds of having depression compared to those without co-morbidity (p = 0.01). The non-Malays had 53% less chance to experience anxiety compared to Malays (p = 0.01). Those with lower monthly household income were more likely to experience stress than those with higher income, the worst was among participants with income of <RM1000 (<USD320) per month (p = 0.02, OR 5.59). Conclusion Negative emotional states with significant severity were common among PLWH, in particularly depression and anxiety. Thus, these psychological problems should be screened regularly especially among those with co-morbidities and financial constraint to allow provision of adequate emotional and social support.